THE IMPLEMENTATION OF DIORAMA MEDIA TO IMPROVE STUDENTS' SPEAKING ABILITIES - Nora Anggraini Nora Anggraini; Misnar Misnar (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2023)
The purpose of this study is to examine the impact of diorama media on students' speaking abilities at SMP Negeri 35 Takengon and assess their response to the use of diorama media for improving speaking abilities. Collaborative Classroom Action Research was employed as the research method, with the researcher working in collaboration with the teacher at SMP Negeri 35 Takengon. The research utilized tests, observation checklists, and questionnaires as the data collection instruments. Analysis of the data revealed that the mean score for students' speaking ability tests was 43.65 in the first cycle and 72.04 in the second cycle. The students' response to the implementation of diorama media yielded a mean score of 3.7, indicating a